Pengaruh Strategi Kepemimpinan Digital UMKM Terhadap Kepuasan Konsumen Di Era Digital - Nungki Agustin; Munawaroh Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of digital leadership strategies on MSME customer satisfaction in the digital era. In the era of digital transformation, digital leadership plays a crucial role in driving innovation and adaptability of MSMEs to meet consumer needs. This research uses a descriptive quantitative approach by distributing questionnaires to MSME consumers who use digital leadership strategies. Data analysis was conducted using linear regression test and Pearson correlation test. The results showed a positive and significant relationship between digital leadership and customer satisfaction. The calculated F value of 17,993 and a significance level of 0.001 indicate that an effective digital leadership strategy can increase customer satisfaction. This finding underscores the importance of utilizing digital technology for MSMEs to create a more personalized customer experience, increase consumer loyalty, and strengthen competitiveness in the market. This study recommends MSME leaders to continue developing capabilities in digital technology to achieve business sustainability.